Identifying qualitative effects of different grazing types on below‐ground communities and function in a long‐term field experiment. (23rd July 2014) - Macdonald, Catriona A.; Crawley, Michael J.; Wright, Denis J.; Kuczynski, Justin; Robinson, Lucinda; Knight, Rob; Al‐Soud, Waleed Abu; Sørensen, Søren J.; Deng, Ye; Zhou, Jizhong; Singh, Brajesh K.
Summary: Herbivory is an important modulator of plant biodiversity and productivity in grasslands, but our understanding of herbivore‐induced changes on below‐ground processes and communities is limited. Using a long‐term (17 years) experimental site, we evaluated impacts of rabbit and invertebrate grazers on some soil functions involved in carbon cycling, microbial diversity, structure and functional composition. Both rabbit and invertebrate grazing impacted soil functions and microbial community structure. All functional community measures (functions, biogeochemical cycling genes, network association between different taxa) were more strongly affected by invertebrate grazers than rabbits. Furthermore, our results suggest that exclusion of invertebrate grazers decreases both microbial biomass and abundance of genes associated with key biogeochemical cycles, and could thus have long‐term consequences for ecosystem functions. The mechanism behind these impacts are likely to be driven by both direct effects of grazing altering the pattern of nutrient inputs and by indirect effects through changes in plant species composition. However, we could not entirely discount that the pesticide used to exclude invertebrates may have affected some microbial community measures. Nevertheless, our work illustrates that human activity that affects grazing intensity may affect ecosystem functioning and sustainability, as regulated by multi‐trophic interactions between above‐ and below‐ground communities.